2007
DOI: 10.3171/jns-07/10/0765
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve lesions associated with missile-induced pseudoaneurysms

Abstract: Whether or not a missile-induced pseudoaneurysm associated with a nerve lesion will be recognized before surgery depends on its location and clinical presentation. The nerves involved almost invariably exhibit a lesion in continuity, but the resulting nerve damage can be severe, particularly if surgery is delayed for more than 3 to 4 days after neurological worsening has begun. A successful outcome may be expected if an appropriate surgical technique (neurolysis or grafting) is chosen on the basis of the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
0
11
1
1
Order By: Relevance
“…In our series, four of nine patients (44.4%) had sustained a stab injury, another four patients (44.4%) had sustained a traffic accident injury, and the other one patient (11.1%) had sustained a fall accident injury. Thus, in contrast to previous reports [1] , [2] , [9] , [10] , [11] , [12] we found that violent blunt trauma, e.g., from traffic accidents, was a notable cause of traumatic pseudoaneurysms of the axillary artery combined with brachial plexus injury.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In our series, four of nine patients (44.4%) had sustained a stab injury, another four patients (44.4%) had sustained a traffic accident injury, and the other one patient (11.1%) had sustained a fall accident injury. Thus, in contrast to previous reports [1] , [2] , [9] , [10] , [11] , [12] we found that violent blunt trauma, e.g., from traffic accidents, was a notable cause of traumatic pseudoaneurysms of the axillary artery combined with brachial plexus injury.…”
Section: Discussioncontrasting
confidence: 99%
“…Traumatic pseudoaneurysms of the axillary artery are rarely encountered in civilian clinical practice, with case reports comprising the majority of the literature on this condition. Penetration trauma, such as stab wounds and gun missile wounds, is the most common cause of pseudoaneurysms [9] . In our series, four of nine patients (44.4%) had sustained a stab injury, another four patients (44.4%) had sustained a traffic accident injury, and the other one patient (11.1%) had sustained a fall accident injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Als weitere Beispiele sind zu nennen die Nervenverletzungen, die bei offenen Frakturen, onkologischen Erkrankungen oder einfachen Schnittwunden auftreten. Nicht unerwähnt bleiben sollten an dieser Stelle auch die iatrogenen Verletzungen peripherer Nerven im Rahmen invasiver Diagnostik oder operativer Eingriffe [14,23].…”
Section: Diskussionunclassified